Indigenising anthropology with Guattari and Deleuze. - Glowczewski, Barbara (Plateaus., 2019)
This collection of essays charts the intellectual trajectory of Barbara Glowczewski, an anthropologist who has worked with the Warlpiri people of Australia since 1979. Inspired by the art and struggles of different Indigenous people and other discriminated groups, especially women, she delivers a radical anthropology.